Linear optimization of soil mixes in the design of vertical cut-off walls - Dungca, Jonathan R. (Animo Repository, 2018)
In order to prevent the contamination of surrounding groundwater in a landfill, cut-off walls were recommended. Cut-off walls are walls utilized when there is a need to restrict horizontal movement of liquids. Currently, the factors in designing cut-off walls are effective permeability, and relatively inexpensive materials in containing contaminants. It was suggested to provide a mix of 96% soil and 4% bentonite in the design of cut-off walls, but bentonite is relatively expensive, thus the viability of fly ash as a replacement for bentonite was considered. Soil mixtures were proposed and rigorous laboratory tests was performed to determine the individual properties. Tests such as specific gravity tests, Atterberg limit tests (liquid limit, plastic limit and plasticity index), emax and emin test/relative density tests, particle size analyses, microscopic characterizations, elemental composition tests and permeability tests were performed to garner data, and were utilized for the model. A linear optimization model was generated to achieve the least cost with the minimum required permeability. The minimum permeability requirement for the cut-off wall was achieved by providing various mixtures for soil-bentonite-fly ash. © 2018, Int. J. of GEOMATE.